Is Golf a Contact Sport? Protection of the Spine and Return to Play After Lumbar Surgery. Issue 2 (March 2022) - Haddas, Ram; Pipkin, William; Hellman, Dan; Voronov, Leonard; Kwon, Young-Hoo; Guyer, Richard
Study Design: Narrative review. Objective: To address the gap in the literature on specific return to play protocols and rehabilitation regimens for golfers undergoing lumbar spine surgery with a high impact swing. Methods: This review did not involve patient care or any clinical prospective or retrospective review of patient information and thus did not warrant institutional review board approval. The available literature of PubMed, Medline, and OVID was utilized to review the existing literature. Results: Studies have shown that the forces through the lumbar spine in the modern-era golf swing are like other contact sports. Methods of protecting the lumbar spine include proper swing mechanics, abdominal and paraspinal musculature strengthening and flexibility as well as physical fitness. There are a variety of treatment options available to treat lumbar spine pathology each with a different return to play recommendations from doctors in the field. Conclusions: With the introduction of a high impact, modern-era swing to the game of golf, the pathology is seen in the lumbar spine of both young, old, professional, and amateur golfers with low back pain are similar to other athletes in contact sports. Surgery is effective in returning athletes to a similar level of play even though no protocols exist for an effective and safe return. There have been many studies conducted to determine appropriate treatment and return to play for these injuries, but there is a gap in the literature on specific return to play protocols and rehabilitation regimens for golfers undergoing lumbar spine surgery with a high impact swing. As return to competitive play is important, especially with professional golfers, studies combining the use of swing mechanics changes, rehabilitation regimens and the type of surgery performed would be able to provide some insight into this topic now that golf may begin to be considered a contact sport.